Microbial community-based protein production from wastewater for animal feed applications - Vethathirri, Ramanujam Srinivasan (2021)
Single cell protein (SCP) derived from microbial biomass represents a promising source of protein for animal feed additives. While microbial community-based approaches to SCP production using nutrient-rich wastewaters incur lower costs than traditional single organism-based approaches, they have received little attention. This review focuses on SCP production using wastewaters with an emphasis on food-processing wastewaters. An elemental carbon-to-nitrogen ratio ranging from 10 to 20 is recommended to promote a high microbial biomass protein yield. Proteobacteria was identified as the most prevalent phylum within SCP-producing microbial communities. More research is needed to determine the composition of the microbial community best suited for SCP production, as well as its relationship with the microbial community in influent food-processing wastewaters. Remaining challenges are target protein and essential amino acids content, protein quantification and biomass yield assessment. The review presents bioreactor design considerations towards defining suitable operating conditions for SCP production through microbial community-based fermentation.